Enhancement of conception rate through luteotropic hormones with special reference to metabolic, biochemical profile and cervical mucus properties in non-infectious repeat breeding Murrah buffaloes - Kumbhar, Umesh Balkrishna; Deshpande, Vaibhav Prakashrao; Gulavane, Sarita Ulhas; Gaikwad, Sandeep Mahadeo (Buffalo Bulletin, 2020)
The present research work was carried out to evaluate efficacy luteotropic hormones with special refence to metabolic, biochemical profile and cervical mucus properties in non-infectious repeat breeding Murrah buffaloes. The research was conducted at Department of Animal Reproduction, Gynaecology and Obstetrics, Bombay Veterinary College, Mumbai and Murrah buffalo dairy farms of Aarey Colony, Goregaon, Mumbai. Out of 60 repeat breeding Murrah buffaloes of 6 to 8 years old, thirty two pluriparous Murrah buffaloes of non-infectious origin were selected on the basis of white side test for the present study. The incidence of infectious and non-infectious repeat breeding buffaloes was 44.66% and 53.33%, respectively in 60 repeat breeding buffaloes of Aarey colony. The cervical mucus properties, serum metabolic and biochemical profile was performed in 32 Murrah buffaloes. The overall mean serum phosphorus, glucose, BUN concentration was 4.29±0.13 mg/dL, 45.51±0.91 mg/dL, 13.37±0.46 mg/dL respectively. In present study, out of 32 non-infectious repeat breeder buffaloes, 21 (65.63%), 10 (31.25%) and 1 (3.12%) buffaloes showed typical, atypical and nil fern pattern of cervical mucus, respectively. The mean pH of cervical mucus in conceived buffaloes was 7.54±0.09 while in non-conceived buffaloes it was 7.44±0.06. Out of 32 non-infectious repeat breeder buffaloes, 16 (50.00%), 6 (18.75%) and 10 (31.25%) buffaloes showed thin and thick consistency of cervical mucus discharge, respectively. All the 32 (100%) non-infectious repeat breeder buffaloes of all the four groups showed clear cervical mucus. The Murrah buffaloes were randomly devided into four groups with eight animals in each group. The Group I was treated with Inj. GnRH 20 μg while Group II and Group III were treated with Inj. hCG 1500 IU and 3000 IU, respectively on day 7 after Artificial Insemination. Group IV was kept as control. The pregnancy was confirmed after 2 months of Artificial Insemination by per rectal examination. In present research work, the conception rates in Murrah buffaloes of Group I, II, and III were 50.00% (4/8), 50.00% (4/8) and 62.50% (5/8), respectively. In Group IV none of the eight Murrah buffaloes was conceived. The overall conception rate in the present study was 40.67% (13/32). From present research it is concluded that the higher conception rate can be expected when non-infectious repeat breeding buffaloes shows typical fern pattern with thin consistency of mucus, alkaline pH and colour was transpernt. The serum biochemical estimation of blood urea nitrogen, glucose and phosphorus was in normal concentration. Also there was no significant difference in the values of these components among conceived and non-conceived buffaloes. All the three blood constituents were found to have no effect on conception. The hormones GnRH and hCG both can be used to treat the repeat breeding Murrah buffaloes of non-infectious origin when administered on day 7 after artificial insemination. The efficacy of human chorionic gonadotropin 3000 IU is more than that of GnRH 20 μg and hCG 1500 IU to enhance the conception rate. The treatment protocols of present studies were found beneficial to increase the serum progesterone concentration when given on day 7 after AI therefore administration of hCG or GnRH on day 7 after AI could be used as a management tool to enhance the progesterone concentration and thereby to improve conception rate in non-infectious repeat breeding Murrah buffaloes.